TYPES OF ARBITRATION COURTS AND THEIR CLASSIFICATION (TSUL LEGAL REPORT, 2026)
In the context of modernization and reform in the world, the ongoing reforms in the field of law enforcement and the judiciary is primarily aimed at the full protection of human rights, freedoms and legitimate interests. Over the past period, a wide range of organizational and legal measures have been taken to gradually strengthen the judiciary, ensure the independence of the judiciary, and reliably protect human and civil rights and freedoms. There are also problems with arbitration today. This article examines the classification of arbitration courts as one of the types of alternative dispute resolution and their types with an analysis of foreign experience. The types of arbitration courts have been studied in accordance with their classification in accordance with our national legislation, and appropriate proposals and recommendations have been made. This article addresses these issues.